Effect of Boron Nitride Addition on the Microstructure and Mechanical Properties of PM Steels - ERDEN, Mehmet Akif; TÜRKMEN, Mustafa; KARABULUT, Hasan; GÜNDÜZ, Süleyman (Afyon Kocatepe Üniversitesi, Fen ve Mühendislik Bilimleri Dergisi, 2017)
In this work, the effects of boron nitride additions on the microstructures and tensile behaviours of microalloyed powder metallurgy (PM) steels were investigated. The microstructure of the microalloyed PM steels was characterised by optic microscope, SEM and EDS. Results indicated that the addition of boron nitride in the percentage of 0.1 and 0.2 increases the yield strength (YS) and ultimate tensile strength (UTS) of the PM steels in the sintered conditions. Elongation also tends to improve with increasing boron nitride content. In addition, the presence of boron nitride in different proportion prevented grain growth during sintering or cooling after sintering. However, a further increase in BN to 0.5 wt.% reduced the yield strength (YS), ultimate tensile strength (UTS), percentage elongation and hardness due to higher amount of precipitation strengthening.

Bu çalışmada, Mikroalaşımlı Toz metal (TM) çeliklerin mikroyapı ve çekme davranışları üzerine bor nitrür ilavesinin etkileri incelenmiştir. Mikroalaşımlı TM çeliklerin mikroyapıları optik mikroskop, SEM ve EDS analizleri kullanılarak karakterize edilmiştir. Sonuçlar; yüzde 0,1 ve 0,2 oranında bor nitrür ilavesinin TM çeliklerin akma dayanımını (YS) ve çekme mukavemetini (UTS) artırdığını göstermiştir. Ayrıca % Uzama oranı bor nitrür ilavesinin artmasıyla artma eğilimindedir. Buna ek olarak, farklı oranda bor nitrür varlığı sinterleme sırasında veya sinterleme sonrasında tane büyümesini engellemiştir. Ancak ağırlıkça % BN oranını 0,5 olduğunda akma dayanımı (YS), çekme dayanımı (UTS), % uzama ve sertlik değeri çökelme sertleşmesine bağlı olarak azalmıştır.
Toz Metal Çeliklerin Mikroyapı ve Mekanik Özelliklerine Bor Nitrürün Etkisi
Keywords: PM Steels; Boron Nitride; Microstructure; Mechanical Properties